Pengaruh Kenaikan Pangkat Dan Jabatan Terhadap Peningkatan Kinerja Pegawai - Tri Wahyuny Irianty; Shonhadji Sholeh (STAI Publisistik Thawalib Jakarta, 2023)
The aim of the research is to find out how much influence promotions and positions have on employee performance at the Pasuruan Regency Ministry of Religion Office. Quantitative research method through a correlational approach. Data collection techniques using questionnaires. Data analysis techniques: descriptive test, validity and reliability test, normality test, multicollinearity test, autocorrelation test, t test, and F test. The research results stated that promotions, positions, and improvements in employee performance were in the good category, this was because employees experienced an increase in the responsibilities given to them after promotions in rank and position. There is a low influence due to the absence of a significant increase in the amount of work successfully completed by employees after a promotion in rank and position of 0.4%, there is a significant influence between promotion in position and an increase in employee performance of 69.6%, and there is an influence The significant difference between promotion and position is the increase in employee performance by 9.7%.